2010
DOI: 10.1149/1.3455046
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Patterned Pt Array Electrodes for Triple Phase Boundary Study in Low Temperature SOFC

Abstract: This paper describes the fabrication and investigation of morphologically stable model electrode structures with well-defined and sharp platinum/yttria-stabilized zirconia ͑YSZ͒ interfaces to study geometric effects at triple phase boundaries ͑TPBs͒. A nanosphere patterning technique using monodispersed silica nanoparticles, which are applied to the YSZ surface by the LangmuirBlodgett method, is employed to deposit nonporous platinum electrodes containing close-packed arrays of circular openings 300-400 nm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 44 publications
1
29
1
Order By: Relevance
“…Many studies to lower the electrolyte resistance of SOFCs have been conducted by exploring alternative electrolyte materials and by developing cell structures with thin film technologies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Recently, ceria-based electrolyte materials have received attention due to their high ionic conductivity and reactivity at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies to lower the electrolyte resistance of SOFCs have been conducted by exploring alternative electrolyte materials and by developing cell structures with thin film technologies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Recently, ceria-based electrolyte materials have received attention due to their high ionic conductivity and reactivity at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Some research groups have fabricated nano-scale thin film SOFCs with freestanding membranes by applying microelectromehanical system techniques [9][10][11][12][13][14][15]. They have also demonstrated that the electrode/electrolyte interfacial area of the freestanding thin film SOFC can be drastically increased by various nano-scale fabrications [11][12][13]. However, the freestanding structures with only tens of nanometer thick membranes will inevitably suffer from thermomechanical issues.…”
Section: Introductionmentioning
confidence: 99%
“…The porous silver nano-mesh was created by a recipe specified in our previous publication (11). As a result, well-defined 500~600 nm diameter pores were patterned on the silver thin film in a close-packed hexagonal array.…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al reported a 0.7 mW/cm 2 peak power density at 450°C for a conventionally tested SOFC device with a commercial 8-YSZ substrate and 80-nm-thick sputtered Pt electrodes. [1] It performed similarly to this study's "no pretreatment" device tested at the same temperature. This study's FG/air-cycled device, on the other hand, had a 10× higher peak power density than the literature device at 450°C.…”
mentioning
confidence: 99%
“…However, a major difficulty associated with nanoporous Pt electrodes, even at low temperatures, is the tendency for grain coarsening and film break-up on the surface of electrolytes such as yttria-stabilized zirconia (YSZ). [1][2][3][4][5][6] These morphological changes can result in severe loss of triple-phase boundaries (TPBs -regions where gas, electrolyte, and electrode coexist), which in turn increases the activation loss and overpotential required to run the fuel cell. At low-to-moderate temperature, slow cathode kinetics tend to limit the performance of SOFCs, and high TPB area is a key structural feature for efficient O 2 reduction and oxygen ion incorporation into the electrolyte at the cathode side of the cell.…”
mentioning
confidence: 99%